ZnO-mediated solar photocatalytic degradation of azo dye - Siti Zharifah Roba'ai (School of Environmental Engineering , University Malaysia Perlis, 2010)
Wastewaters generated from the textile industry contain large amounts of azo dyes which, owning to their non-biodegradability, toxicity and potential carcinogenic nature, constitutea major threat to the surrounding ecosystem. Environmental concerns and the need of meeting the stringent international standards for rejecting wastewaters has made the development of novel, efficient and low cost methods for the purification of textile aqueous effluents an issues of major importance. ZnO mediated solar photocatalytic has been shown to be a potentially advantageous process as it may lead to complete mineralization at ambient conditions with the use of solar light as the energy sources. In the present study, the photocatalytic degradation of a model textile azo dye (Acid Orange 7, AO7) in aqueous solution is investigated with the use of ZnO photocatalyst.